Avenues within the gut-liver-brain axis linking chronic liver disease and symptoms - Nguyen, Henry H.; Swain, Mark G. (Frontiers in Neuroscience, 2023)
Symptoms of fatigue, social withdrawal and mood disturbances are commonly encountered in patients with chronic liver disease and have a detrimental effect on patient quality of life. Treatment options for these symptoms are limited and a current area of unmet medical need. In this review, we will evaluate the potential mechanistic avenues within the gut-liver-brain axis that may be altered in the setting of chronic liver disease that drive the development of these symptoms. Both clinical and pre-clinical studies will be highlighted as we discuss how perturbations in host immune response, microbiome, neural responses, and metabolites composition can affect the central nervous system.